Extensive supraglottic mass—An anesthetist’s nightmare - K Chethan Hebbar; Abhishek Nagarajappa; M Chandramouli; Anvi (Saudi Journal of Anaesthesia)
Supraglottic carcinoma presents significant challenges in airway management during general anesthesia. We report a case of a 26-year-old female with extensive supraglottic growth undergoing a biopsy. Awake fiber-optic intubation was performed due to the risk of airway obstruction and difficulty with direct laryngoscopy. Upper airway anesthesia was achieved with nebulized lignocaine and the spray-as-you-go technique. Successful intubation was followed by an uneventful surgical procedure and a smooth recovery. This case highlights the efficacy and safety of awake fiber-optic intubation in managing difficult airways in patients with supraglottic tumors, minimizing complications and enhancing patient outcomes.